Pendekatan Sosiologi Dalam Studi Hukum Islam - Marsudi Marsudi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2004)
Abstract This study aims to analyze the role of sociological approach in Islamic law studies and its implications for the understanding and application of sharia in society. The method used is juridical-sociological research with a descriptive-analytical approach, through literature studies and studies of social phenomena that influence the dynamics of Islamic law. The results show that the sociological approach helps to understand Islamic law not only as a normative norm, but also as a system that develops in social interaction. Factors such as culture, economy, and social change influence the implementation of Islamic law in various contexts. Therefore, the integration of a sociological approach in the study of Islamic law allows for a more comprehensive and responsive analysis of the reality of society, so that Islamic law can be applied in a more relevant and equitable manner.